Development of a high-throughput screen for the study of CRISPR spacer acquisition - Braithwaite, Jack (2021)
Bacteria are in an ever-evolving arms race to survive against invasion from foreign genetic elements. One mechanism of defence is the CRISPR-Cas system of adaptive immunity. Through CRISPR-Cas, cells store memories of previous invaders as DNA fragments, or spacers, in a genomic array of repeats. Once transcribed, these spacers guide CRISPR associated (Cas) proteins in the sequence-specific destruction of matching invaders.